Descartes on Corporeal Substances - Zerbudis, Ezequiel Jorge (2015)
I defend in this paper the following two theses: first, that Descartes was a Pluralist as regards extended substances, that is, that for him the extended world includes a plurality of bodies, including ordinary objects, each of which may be adequately described as a substance; and that for him the notion of substance is a rather slim notion, making no specific requirements as regards individuation or persistence conditions, and determining therefore no strict constraints on the kind of material objects that may count as substances. In short, I will be arguing for a certain view concerning the extension of the phrase ‘extended substance’ by defending a specific view of what ‘substance’ means.